The Utilization of Artificial Intelligence as a Technological Revolution Transforming the Film Industry - Madhini, Intan Tamara; Rahmah, Nurliya Ni'matul; Saudi, Yusron (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This research aims to describe and analyze the use of artificial intelligence (AI), specifically through the Suno.AI platform, in the production of film backsounds by students. The issues raised in this research are how AI can contribute to the creative process of making background music, and to what extent this technology can fulfill the emotional and narrative needs of a film. This research uses a descriptive qualitative approach by adopting the media equation theory, which states that humans often treat media, including AI, as if they were real social actors. The results show that the use of AI, specifically Suno.AI, is able to accelerate the process of creating music composition by generating relevant initial drafts according to the visual and emotional context of the film, as applied in the production of Kata Lana. This platform is not only efficient in reducing production time, but also enables a broader exploration of musical ideas. However, there are some challenges, such as AI's limitations in creating complex emotional nuances and unique variations of musical styles. While AI is capable of producing technical compositions, the role of a human composer is still necessary to give a personalized and immersive touch to the final result. The findings confirm that collaboration between humans and AI can improve production efficiency while maintaining artistic quality in the film industry.